Rancang Bangun Layanan Cloud Computing Berbasis IaaS Menggunakan Virtualbox - Muhammad Faizal Afriansyah; Adian Fatchur Rochim; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2015)
Today, the growth of technology is very fast and a lot of technology that can facilitate users in helping their activity is made. A technology need a server to store both systems and users data. More users needed more servers to store user data. The server room became full and needed the extra space so that it required high cost to build the server and the server space itself. The purpose of this research is to create an IaaS based server virtualization that is connected to a router, switch, virtual client and administrator with VirtualBox application. The purpose of this research can be achieved by designing an appropriate research’s methodology. There are 5 stages of implementation/methodology in building virtualization server at this research which are the system definition, requirements specification, system configuration, system testing, and system analysis. First, phase of the definition system is by describing a system of early identification, system requirements and network topology on the implemented system. The second phase is the specification requirements to determine specifications hardware and software. The hardware consists of a computer with resources 8GB RAM and AMD Phenom II X6 as a processor. The software consists of VirtualBox and operating systems. The third stage is the system configuration to declare the source code in application on each server, routers and switches to perform the function of each device. The final stage is system testing and system analysis by checking the system is ready to use and works the best. Results in this research show IaaS-based server virtualization can be connected to display a web page on all clients through virtual switches and routers on a computer.